Future Competencies and E-Tutor Competencies: A Chance for Higher Education Institutions to Support Their Student Staff - Lisa-Marie Langesee (International School for Social and Business Studies, 2022)
Purpose: E-tutors often participate in collaborative online international learning (COIL) settings and guide students in group work and related learning processes. They moderate, organize, and observe the group and individual learning processes and are often students' first point of contact. This support requires several competencies, which are also largely reflected in the so-called future skills. Thus, it seems sensible to examine these competencies more closely and promote them to enhance the course experience and support for students in COIL settings on the one hand and to make student e-tutors fit for the modern working world on the other. Study design/methodology/approach: As a starting point for this project, a comprehensive systematic literature analysis on e-tutor competencies and qualifications was conducted in Langesee (2023). A competency ranking and task-based competency profile for e-tutors in higher education were developed during this research. To investigate the validity and practicability of these artifacts, an evaluation was conducted with 16 international experts and practitioners (e-tutors) using a questionnaire. Findings: The competencies identified in Langesee (2023), the ranking, and the profile created were recognized as helpful and practical. Additional comments from respondents allowed both artifacts to be revised and expanded. The three most relevant competencies of the nine detected are communication, pedagogical and social competencies. Originality/value: The resulting artifacts can be used in the next step as a basis for a self-evaluation tool (SET), enabling e-tutors to assess their competence equipment. Based on this, individual instruments will be recommended to initiate possible improvements.